Faktor yang Berdampak terhadap Kinerja Guru MAN di Kota Rembang - Ardhanari, Aria Anggira; Tahwin, Muhammad (J-MAS (Jurnal Manajemen dan Sains), 2024)
The motive of this observe is to expose the impact of labor subject, organizational lifestyle and motivation at the performance of instructors in Madrasah Aliyah Negeri 1 Rembang. the academics of Madrasah Aliyah Negeri 1 Rembang have been used on this observe. A sample of 50 instructors changed into used on this study. statistics analysis strategies the usage of multiple linear regression analysis. The results confirmed that work discipline and motivation had a substantial nice effect on instructor overall performance in Madrasah Aliyah Negerti 1 Rembang, and organizational lifestyle had a negative and insignificant impact on instructor overall performance in Madrasah Aliyah Negerti 1 Rembang. The adjusted R-squared value is 0.534. as a result, it may be interpreted that 53.4% of teaching and work results can be defined by means of 3 independent variables, which are work discipline, organizational subculture and motivation. The final 46.6% may be defined by using different variables not investigated on this observe.